2016
DOI: 10.1021/acs.jmedchem.6b01055
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Chemical Probe Bisamide (CCT251236): An Orally Bioavailable Efficacious Pirin Ligand from a Heat Shock Transcription Factor 1 (HSF1) Phenotypic Screen

Abstract: Phenotypic screens, which focus on measuring and quantifying discrete cellular changes rather than affinity for individual recombinant proteins, have recently attracted renewed interest as an efficient strategy for drug discovery. In this article, we describe the discovery of a new chemical probe, bisamide (CCT251236), identified using an unbiased phenotypic screen to detect inhibitors of the HSF1 stress pathway. The chemical probe is orally bioavailable and displays efficacy in a human ovarian carcinoma xenog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 102 publications
0
72
0
Order By: Relevance
“…Therefore, we initially designed a synthetically tractable 15-atom linker that we predicted would not affect the affinity of the PDP for the isolated target proteins. 26 Analysis of the crystal structure of the chemical probe 1 bound to pirin ( Figure 1 , PDB 5JCT) 11 suggested that the solvent-exposed solubilizing group vector should be amenable to linker attachment. We selected a CRBN-targeting thalidomide ligand as the basis of our E3 ligase binding motif due to its low molecular weight.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we initially designed a synthetically tractable 15-atom linker that we predicted would not affect the affinity of the PDP for the isolated target proteins. 26 Analysis of the crystal structure of the chemical probe 1 bound to pirin ( Figure 1 , PDB 5JCT) 11 suggested that the solvent-exposed solubilizing group vector should be amenable to linker attachment. We selected a CRBN-targeting thalidomide ligand as the basis of our E3 ligase binding motif due to its low molecular weight.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Trapping the carbonylation intermediate with 2-(trimethylsilyl)ethan-1-ol gave the (trimethylsilyl)ethyl ester 7 , 29 which facilitated TBAF-selective hydrolysis. Amide coupling to the previously described bis-aniline derivative 8 ( 11 ) was followed by hydrolysis of the aliphatic linker ester to give acid 9 . Final amide coupling to the CRBN-targeting derivative 4 gave the first-generation pirin-targeting PDP 3 in 10 steps and 0.4% overall yield.…”
Section: Results and Discussionmentioning
confidence: 99%
“…13,16,[30][31] However, to pharmacologically verify that pirin is involved in TGF- dependent gene expression, we used CCT251236, the previously published pirin inhibitor. 28 Human primary dermal fibroblasts were activated with TGF- for 24 hours with or without CCG-222740 or CCG-257081 as well as CCT251236. All three compounds significantly reduced TGF induced ACTA2 expression ( Figure 4A).…”
Section: Inhibition or Ablation Of Pirin Reduces Tgf- Induced Profibmentioning
confidence: 99%
“…The SRE.L Luciferase reporter contains several SRF binding sites that were modified to be dependent on MRTF, but lack responsiveness to ETS factors. 1 CCT251236 has nM potency in a cell-based assay to identify inhibitors of Heat Shock Factor 1 transcription and binds to pirin in vitro with a KD of 44 nM as measured by SPR 28. CCT251236 had a remarkable effect on SRE.L luciferase expression, with an IC50 of 3.3 nM, without affecting luciferase catalytic activity directly (Figure 3Aand SupplementalFigure 3).…”
mentioning
confidence: 99%
“…The fully autonomous beamline MASSIF-1 at the ESRF not only automates the process of sample handling but also runs complex crystal location, characterisation and decision making routines for every sample processed Svensson et al, 2015). This level of automation allows a wide range of projects to use the beamline, from those that require extensive screening to find the best diffracting crystal Na et al, 2017;Naschberger et al;Sorigué et al, 2017;Xu et al, 2018) to small molecule fragment screening (Cheeseman et al, 2017;Hiruma et al, 2017) and experimental phasing at high and low resolutions (Kharde et al, 2015;Schulze et al, 2018). The routines optimise data collection by centring crystals using X-ray diffraction quality to determine the location of the best volumes to centre , measuring crystal volumes to dynamically adapt the beam dimeter to match the crystal and also to determine the dose the sample can receive before sustaining significant radiation damage Svensson et al, 2015;Zeldin et al, 2013;Bourenkov & Popov, 2010).…”
Section: Introductionmentioning
confidence: 99%